Farmers' Perception Towards Black Head Ettawa Crossbred Goat in Kaligesing, Purworejo, Indonesia - Guntoro, Budi (Medwell Journals, 2015)
The aims of the research were to analyse the farmers perception of black head Ettawa crossbred goat in Kaligesing and the factors wich influenced farmers perception of black head Ettawa goat kaligesing. This research too; used questionnaires and survey methods. Data were collected by distributing 100 questionnaires with interviewed to 100 respondents into 3 different strata areas, the areas in Pandanrejo (upland Kaligesing), Tlogoguo (center Kaligesing), Kaligono (lowland Kaligesing). The farmers perception of black head Ettawa crossbred goat in Kaligesing achieved 68% that means black head Ettawa crossbred goat preffered by farmers in Kaligesing. The result of this research showed that age was significant (p<0.05), experience was very significant (p<0,01), income was significant (p<0,05), gender was significant (P<0.05) and education was not significant (p>0.05) to the farmer’s perception towards black head Ettawa crossbred goat. While, education was not influenced farmers perception of black head Ettawa crossbred goat in Kaligesing. The results which were obtained indicating R2 of equation Y= 80.952-0.489X1-0.576X2+0.786X3+0.005X4+0.005X5 was 0.28.2 that means 28.2% farmers perception could be explained by those variables in the regression equation while 71.8% explained by other factors beyond this study